Vertical displacement time series from GNSS stations in the Po river basin area - Francesco Pintori; Enrico Serpelloni (PANGAEA, 2023)
ASCII files reporting the daily GNSS vertical ground displacement time series, in the Eurasia-fixed reference frame, from January 2010 to September 2022 of continuous stations located in the Po river basin. The time series are obtained by analyzing the raw GPS observations using the GAMIT/GLOBK (version 10.71) software, following the standard procedures of the repro2 IGS reprocessing scheme (http://acc.igs.org/reprocess2.html). This is part of a large processing effort, including>4000 stations in the Euro- Mediterranean and African regions (Serpelloni et al., 2022), where sub-networks, made up of <50 stations dynamically and optimally selected based on daily data availability, are processed independently with GAMIT and later tied together using common sub-net tie sites and IGb14 core stations using the GLOBK software. This time series are used to study the effect of the drought occurring since 2021 in Northern Italy. The columns of the files are: Time, U, Su, site, long, lati, representing, respectively, epoch (in decimal years), displacement in the Up component (in mm), uncertainty (one standard deviation) of the Up component (in mm), Station ID, Longitude of the station (°), Latitude of the station (°).